#TITLE_ALTERNATIVE# - YOHANNES MANURUNG NIM: 22716006, HERBERT
Basically a Fault can act as a flow path of the fluid (conduit), boundary, or a combination of the two so that it can be a pathway and also can seal the fluid flow through it. Groundwater will generally flow to a fault zone because this zone has a large hydraulic conductivity value. This is influenced by two factors, namely groundwater gradient and concentration of force around the fault which causes the presence of a high permeability zone around the fault.Based on the description above, the purpose of this study was to determine whether the Lembang’s fault is a conduit based on hydrogeochemical characterization which includes dissolved trace elements, 13C stable isotopes from the springs found in the study area.Based on the results of grouping of isotope values, it was found that Maribaya hot springs are in the Marine DIC, Limestone and Dolostone groups, the genesis of Maribaya hot springs comes from marine sediments or limestones, while outcrops in the study area do not show the presence of marine sedimentary rocks or limestones. This indicates that the presence of marine sedimentary rocks or limestones comes from Tertiary rocks located in the lower layers of Quaternary rocks, where the Lembang’s Fault is the main factor influencing the presence of hot water contact from Maribaya hot springs with Tertiary rocks.